Study on pressure‐controlled sliding sleeve of jet breaking for natural gas hydrate mining based on throttle pressure drop principle. Issue 5 (17th January 2020) - Tang, Yang; Yao, Jiaxin; He, Yin; Sun, Peng; Jin, Xin
Abstract: In order to reduce operating cost of deep‐sea natural gas hydrate (NGH) solid‐state fluidization mining (SSFM), a device for controlling opening and closing of jet nozzles is required. It is required to meet the specifications of work process and is not affected by changes in water depth and well depth. Therefore, a design scheme of a pressure‐controlled sliding sleeve (PCSS) based on the principle of throttling pressure drop is proposed. The nozzles opening and closing process is controlled by flow rate control and is not affected by environmental pressure. Using computational fluid dynamics software, the corresponding control equations are solved by finite volume method and the pressure drop and axial force generated by different flow rates of drilling fluid flowing through different structural sliding cores are obtained. According to simulation analysis results and actual working conditions, a relatively good set of sliding core structural parameters is preferred. According to structural parameters of this group, the prototype of PCSS was machined and throttle pressure drop principle verification experiment and section pressure difference principle exclusion experiment were carried out to verify the feasibility of the design of PCSS. Through this research, it can help to promote the application of the throttling pressure drop principle in controllable oil drilling and completion tools. Abstract : In order to reduce the number of drilling times and reduce the operating cost, this paper innovatively designed a pressure‐controlled sliding sleeve for solid‐state fluidized mining of natural gas hydrate based on the throttling pressure drop principle. The feasibility of the tool was verified by the combination of simulation analysis and experiment.